The Effect of Social Commerce Construct on Consumer Trust and Purchase Intention - Vora Intan Cahayani; Ai Lili Yuliati (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
This research was motivated by problems related to Social Commerce Construct of e-commerce JD.ID in Indonesia. The negative comments (complaint) and low ratings on the rating and review feature on e-commerce JD.ID leads to a decrease in consumer trust and purchase intention of products at e-commerce JD.ID. This research aims conducted to determine the effect of Social Commerce Construct on Consumer Trust and Purchase Intention JD.ID e-commerce users in Indonesia. This research uses a quantitative method with a type of descriptive and causal research. The sampling technique is non-probability sampling type purposive sampling, with the number of respondents as many as 100 people. Data analysis techniques used descriptive analysis and path analysis. The results of this research show that: (1) Social Commerce Construct has a significant effect on Consumer Trust. (2) Social Commerce Constructs have a significant effect on Purchase Intention. (3) Consumer Trust has a significant effect on Purchase Intention. (4) Social Commerce Construct has an indirect effect on Purchase Intention through Consumer Trust.